Ekološko stanje površinskih voda - Kuhar, Urška (Naše okolje, 2018)
Aquatic macrophytes are aquatic plants, large enough to be seen with the naked eye. They comprise different taxonomic groups, namely spermatophytes, pteridophytes, bryophytes and macroscopic algae. Macrophytes are important components of freshwater ecosystems, being involved in sediment stabilization and nutrient cycling, affecting water quality and providing habitat and food for aquatic animals. Distribution and abundance of macrophytes is regulated by many factors and on different spatial scales, from watershed to single habitat. Nutrient enrichment, water quality changes and modification of water and riparian environment alter the composition of macrophyte communities. Thus macrophytes can be used as indicators of environmental conditions. They are mainly used as trophic status indicators. River Macrophyte Index (RMI) and Slovenian Macrophyte-based Index for Lake Ecosystems (SMILE) are used for the assessment of trophic status of rivers and lakes on the basis of macrophytes in Slovenia. Both indices are based on presence and abundance of indicator taxa.
Keywords: ekosistemi; hidrologija; makrofiti; površinske vode